Pengaruh Kinerja Keuangan terhadap Pertumbuhan Penjualan Perusahaan Otomotif pada Masa Pandemi dengan Ukuran Perusahaan sebagai Variabel Moderasi - Elan Kurniawan; Dio Satria BS (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2021)
This study aims to determine the effect of financial performance on sales growth with company size as a moderating variable for automotive companies during the pandemic period on the Stock Exchange for the period 2016 to 2020. Based on the purposive sampling method, there were 12 companies that met the criteria. The results showed that: activity had a significant negative effect on sales growth, profitability had a significant positive effect on sales growth, liquidity had an insignificant positive effect on sales growth, activity moderated by firm size strengthened significant positive effect on sales growth, profitability moderated by firm size weakened no significant negative effect on sales growth and liquidity moderated by firm size weakens no significant negative effect on sales growth